2023
DOI: 10.1128/msphere.00142-23
|View full text |Cite
|
Sign up to set email alerts
|

The role of pneumococcal extracellular vesicles on the pathophysiology of the kidney disease hemolytic uremic syndrome

Abstract: Streptococcus pneumoniae -induced hemolytic uremic syndrome (Sp-HUS) is a kidney disease characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. This disease is frequently underdiagnosed and its pathophysiology is poorly understood. In this work, we compared clinical strains, isolated from infant Sp-HUS patients, with a reference pathogenic strain D39, for host cytotoxicity and further explored the role of Sp-derived extracellular vesicles (EVs) in the pathoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…In terms of the hemolytic profile, the pneumococcal mutants presented in that study, which do not produce H 2 O 2 , show a surprising resemblance to the pspA , pspC , and lytA mutants in the present study. Moreover, H 2 O 2 produced by S. pneumoniae damages human lung cells ( 67 , 68 ). Therefore, the reduced cytotoxicity of the CBPs mutants toward human epithelial and endothelial cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the hemolytic profile, the pneumococcal mutants presented in that study, which do not produce H 2 O 2 , show a surprising resemblance to the pspA , pspC , and lytA mutants in the present study. Moreover, H 2 O 2 produced by S. pneumoniae damages human lung cells ( 67 , 68 ). Therefore, the reduced cytotoxicity of the CBPs mutants toward human epithelial and endothelial cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Schirmer et al reported that the immunostrips of vesicles isolated from patients with latent and active tuberculosis were consistently higher than that of healthy volunteers, which may contribute to the diagnosis of latent TB (Schirmer et al, 2022). In addition, pneumococcal MVs isolated from the blood or urine of patients with Streptococcus pneumoniae-associated hemolytic uremic syndrome contain highly abundant proteins, which can be used as markers of MVs in Sp-HUS and become the a potential diagnostic indicator for Sp-HUS (Battista et al, 2023).…”
Section: Assisting Disease Diagnosismentioning
confidence: 99%